ACSL4 Expression Is Associated With CD8+ T Cell Infiltration and Immune Response in Bladder Cancer - Luo, Wenjie; Wang, Jin; Dai, Xiaoyan; Zhang, Hailiang; Qu, Yuanyuan; Xiao, Wenjun; Ye, Dingwei; Zhu, Yiping (Frontiers in Oncology, 2021)
Objective: This study aimed to explore the role of ACSL4 in CD8+ T cell tumor infiltration and outcomes of bladder cancer (BLCA) patients after immunotherapy. Methods: The correlation between ACSL4 expression and tumor infiltration of immune cells was analyzed using the Tumor Immune Estimation Resource database. The prognostic significance of ACSL4 in BLCA was analyzed using Kaplan–Meier curves. Immunohistochemistry was used to detect CD8+ T cell infiltration in tumors with high and low ACSL4 expression obtained from patients at the Fudan University Shanghai Cancer Center. The relationships between immune checkpoint genes and immune response were analyzed using The Cancer Genome Atlas and IMvigor 210 cohorts. The molecular functions, cellular components, and biological processes involving ACSL4 were explored using Kyoto Encyclopedia of Genes and Genomes and Gene Ontology enrichment pathway analyses. Results: The expression level of ACSL4 was significantly correlated with the infiltration of CD8+ T cells in BLCA tumors (r = 0.192, P = 2.22e-04). Elevated ACSL4 was associated with suppressed tumor progression and better outcomes for BLCA patients. The higher expression level of ACSL4 predicted better immunotherapeutic responses and was associated with higher expression levels of core immune checkpoint genes, including CD274, CTLA4, PDCD1, and LAG3, compared with the low ACSL4 expression group. Conclusion: This study demonstrated for the first time that elevated ACSL4 correlated significantly with CD8+ T cell infiltration and contributed to better immunotherapeutic responses in BLCA patients. Furthermore, ACSL4 serves as a novel biomarker for predicting patient outcomes after immunotherapeutic treatments, which may improve the development of individualized immunotherapy for BLCA.